202 Mitochondrial Dynamics Regulation of Ros and Apoptosis. (6th June 2015) - Sulti, Z Al; McDonald, R; Kingsmore, D; Baker, A; Coats, P
Abstract : Mitochondrial involvement in the control of vascular smooth muscle (VSM) cell proliferation and migration has become more evident than before. Although the mechanisms leading to this control are not fully understood, mitochondrial dynamics and cellular regulation functions can be major players. Studies have revealed that mitochondrial structure and dynamics determines their role played in the cell. 1 Mitochondrial proteins were also found to be involved along with mitochondrial miRNAs. 2 ATP production to energise cellular functions and ROS resulting from the oxidative phosphorylation are also vital in determining mitochondrial role in VSM cell proliferation and migration 3 . Mitochondria also regulate the intrinsic apoptotic pathway resulting in reduction in proliferation 4 . Thus the aim of the current study was to establish a link between mitochondrial dynamics, ROS production and caspase3/7 activation. Blocking mitochondrial fission using DRP-1 inhibitor resulted in a reduction in VSM cell proliferation in response to PDGF (p < 0.05). The same reduced effect was seen with cell migration following their stimulation with PDGF (p < 0.05). Furthermore, addition of DRP-1 inhibitor resulted in both ROS and ATP (p < 0.05). However, caspase3/7 activity was significantly increased following the inhibition of mitochondrial fission. These data, along with our previous data showing down-regulation of miR-21 and an up-regulation of miR-145 following treatment with MDivi-1, highlight an important role played by mitochondrial dynamics in the regulation of VSM cell proliferation and migration through the regulation of miRNA expression and their potential target genes that control cell cycle and apoptosis. References: Chalmers S. et al . Mitochondrial motility and vascular smooth muscle proliferation arterioscler. Thromb Vasc Biol. 2012;32:3000–3011 Barrey E, Saint-Auret G, Bonnamy B, Damas D, Boyer O, Gidrol X. Pre-microRNA and mature microRNA in human mitochondria. PLoS One 2011;6:e20220 Stephen L. Archer, Mardi Gomberg-Maitland. et al . Mitochondrial metabolism, redox signaling, and fusion: a mitochondria-ROS-HIF-1ª¢-Kv1.5 O2 -sensing pathway at the intersection of pulmonary hypertension and cancer. Am J Physiol Heart Circ Physiol. 2008;294 :H570CH578 Ella Bossy-Wetzel and Green DR. Apoptosis: checkpoint at the mitochondrial frontier. Mutation Research. 1999;434 :243C251